Arsenic trioxide combined with transarterial chemoembolization for primary liver cancer: A meta‐analysis. Issue 9 (September 2017) - Lv, Xiu‐He; Wang, Chun‐Hui; Xie, Yan
Abstract: Background and Aim: The benefit of combination therapy of arsenic trioxide (As2 O3 ) and transarterial chemoembolization (TACE) is debated. This meta‐analysis was conducted to determine whether As2 O3 &TACE therapy achieves better therapeutic effects compared with TACE alone for primary liver cancer. Methods: A systematic search of both English and Chinese databases was conducted for randomized controlled trials. The main outcomes were therapeutic responses, survival rates, improvement in quality of life, and adverse events. All data analyses in this study were carried out using Review Manager software and STATA software. Results: Eighteen randomized controlled trials involving 1412 participants were included. The pooled objective response rate was significantly higher in the As2 O3 &TACE group compared with the TACE group (relative risk [RR] 1.36, 95% confidence interval [CI] 1.16–1.58, P  < 0.0001), and the pooled clinical benefit rate was also significantly higher (RR 1.18, 95% CI 1.08–1.29, P  = 0.0002). A higher pooled result was obtained from the combination group for 1‐year survival rate (RR 1.37, 95% CI 1.23–1.53, P  < 0.00001). As2 O3 &TACE therapy was not superior to TACE alone for improvement in quality of life (RR 1.15, 95% CI 0.98–1.36, P  = 0.09). There was no significant difference in the risk of adverse effects. When a subgroup analysis was performed, both administration methods of As2 O3 (intravenous or arterial) were effective for all evaluating indicators except the improvement in quality of life. Conclusions: Adjuvant As2 O3 therapy combined with TACE achieves better therapeutic effects compared with TACE alone. Both the intravenous administration of As2 O3 and the arterial administration of As2 O3 were good options for clinical practice.